Effect of Chlorpyrifos Insecticide On The Ossification of Wader Pari Fish Vertebrae (Rasbora Lateristriata Bleeker, 1854) (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Due to high growth, chlorpyrifos was one of the solution to increase food production. However, this compound is dangerous because it belongs to organophosphate group which blocking the activity of acetylcholinesterase (ache) enzyme and caused nervouse failure to animal. Due to heavy rain this insecticide will run-off and contaminate the body of the river and effect the aquatic live. Wader pari was non-target animal of chlorpyrifos. The purpose of this study was to determine the effect of chlorpyrifos exposure on the behaviour of wader's feeding and swimming response, as well as the morphology and ossification process of the vertebrae. The study was conducted for 7 days. 4 groups of fish were exposed to chlorpyrifos with concentrations of 0, 0.001, 0.005 and 0.01 ppm. Observation of the ossification and morphological process of vertebrae is carried out using AR-Ab bone staining. Observation of wader’s behaviours is carried out using descriptive analysis. It was found that the fish which exposed to chlorpyrifos showed some behavioural abnormalities in swimming and feeding response. Fish exposed to 0.005 ppm chlorpyrifos showed vertebral abnormalities which is haemal kyphosis. Kyphosis refers to Λ-shaped vertebral curvature Fragkoulis et.al, (2019). However, the ossification process that represented by Ar-Ab staining are going well.